Exploring the Antimicrobial and Clinical Efficacy of a Novel Technology in Pediatric Endodontics: An In Vivo Study - Luca De Gregoriis; Tatiane Cristina Dotta; Morena Petrini; Silvia Di Lodovico; Loredana D’Ercole; Simonetta D’Ercole; Domenico Tripodi (Applied Sciences)
Pediatric dentistry continually seeks effective and efficient treatments for young patients, especially within pediatric endodontics, where cooperation can often be challenging. This in vivo study aimed to evaluate the effectiveness of a novel photodynamic therapy (PDT) protocol using a 5-aminolevulinic acid gel (Aladent, ALAD) combined with light irradiation during the endodontic treatment of primary teeth. This study included primary teeth requiring root canal therapy due to carious lesions or trauma, with clinical symptoms suggesting irreversible pulpitis or acute apical periodontitis. Following local anesthesia and isolation with a rubber dam, carious lesions were excavated, and access to the pulp chamber was established. Canal preparation included determining the working length and using a sequence of k-files. Afterward, ALAD gel was applied, and the patients were divided into two groups based on their visit duration (Group A with a single visit, Group B returning after one week). Microbiological analysis was conducted on the samples taken before and after treatment. The findings demonstrated significant antibacterial efficacy of the PDT protocol in reducing root canal bacterial load, suggesting ALAD-based PDT may serve as an alternative to traditional endodontic treatment in cases where retaining primary teeth is essential for orthodontic or strategic reasons. Clinically, improvement in symptoms and fistula resolution were observed. Treatment time, patient compliance, and protocol safety in pediatric applications are also discussed, highlighting the protocol’s potential to enhance clinical outcomes in pediatric endodontics.